pcMSC Modulates Immune Dysregulation in Patients With COVID-19-Induced Refractory Acute Lung Injury - Chen, Mei-Chuan; Lai, Kevin Shu-Leung; Chien, Ko-Ling; Teng, Sing Teck; Lin, Yuh-Rong; Chao, Wei; Lee, Meng-Jung; Wei, Po-Li; Huang, Yen-Hua; Kuo, Han-Pin; Weng, Chih-Ming; Chou, Chun-Liang (Frontiers in Immunology, 2022)
Background and objectives: The novel coronavirus disease 2019 (COVID-19) has been a global pandemic health issue since 30 January 2020. The mortality rate is as high as 50% in critically ill patients. Stem cell therapy is effective in those who are refractory to standard treatments. However, the immune responses that underlie stem cell therapy have not been well reported, particularly, in patients associated with moderate to severe acute respiratory distress syndrome (ARDS). Methods: Intravenous infusion of 2 × 107 placenta-derived mesenchymal stem cells (pcMSCs) (MatriPlax) were administered to five severe COVID-19 patients refractory to current standard therapies at Day 0 and Day 4. Peripheral blood inflammatory markers and immune profiles were determined by multi-parameter flow cytometry and studied at Days 0, 4, and 8. Clinical outcomes were also observed. Results: None of the pc-MSCs treated patients experienced 28-day mortality compared with the control group and showed a significant improvement in the PaO2/FiO2 ratio and in Murray’s lung injury scores, a reduction in serum ferritin, lactate dehydrogenases (LDH), and C-reactive protein (CRP) levels. The cytokine profiles also showed a reduction in IL-1β, IFN-γ, IL-2, IL-6, and an increase in IL-13 and IL-5 type 2 cytokines within 7 days of therapy. Lymphopenia was also significantly improved after 7 days of treatment. Immune cell profiles showed an increase in the proportions of CD4+ T cells (including CD4+ naïve T cells and CD4+ memory T cells subtypes), Treg cells, CD19+ B cells (including CD19+ naïve B cells, CD27+ switched B cells subtypes) and dendritic cells, and a significant decrease in the proportion of CD14+ monocytes (including CD16- classical and CD16+ non-classical subtypes), as well as plasma/plasmablast cells. No adverse effects were seen at the serial follow-up visits for 2 months after initial therapy. Conclusion: pc-MSCs therapy suppressed hyper-inflammatory states of the innate immune response to COVID-19 infection by increasing Treg cells, decreased monocytes and plasma/plasmablast cells, and promoted CD4+ T cells and CD19+ B cells towards adaptive immune responses in severe critically ill COVID-19 patients with moderate to severe ARDS, especially among those who were refractory to current standard care and immunosuppressive therapies.